Experimental exergy, economic and sustainability analyses of the dual-mode evaporative cooler; [Analyses expérimentales portant sur l’énergie, la rentabilité et la durabilité du refroidisseur évaporatif à deux modes] - Kashyap S.; Sarkar J.; Kumar A. (My University, 2025)
The ambient condition varies drastically in the composite climate and the direct evaporative cooling is effective in the dry months; whereas, the regenerative evaporative cooling is effective in the humid months. Hence, seasonal change of the cooling device is needed for effective cooling. In this situation, a dual-mode evaporative cooler (a two-in-one device) is an intelligent choice, which operates in direct mode in the dry months and regenerative mode in the humid months. Hence, this novel evaporative cooler is fabricated in this study and experimental exergy, economic, and sustainability analyses are performed to check the acceptability. Effects of various operating parameters on the performance are experimented in both (indirect and direct) modes of operation. The exergy destruction, exergy efficiency, sustainability index, and specific total cost of the developed device are estimated in both modes of operation. It is found that the exergy efficiency and sustainability index of the regenerative mode are higher while the specific total cost of the direct mode is lower. The developed device is more economical in both operating modes as compared to the conventional air conditioner. © 2021 Elsevier Ltd and IIR